Filling the space between trams and place: Adapting the 'Movement & Place' framework to Melbourne's tram network. (June 2018) - Diemer, Matthew J.; Currie, Graham; De Gruyter, Chris; Hopkins, Ian
Abstract: Melbourne's legacy tram network is being modernised including redesign of over 1700 tram stops to provide level access boarding to comply with Australia's Disability Discrimination Act. This presents a significant opportunity to reimagine how tram corridor streetscapes can function as places that build upon neighbourhood identity and sustain local economic activity. However, the literature on the connection between transport infrastructure and place quality is small and relatively new. This is particularly true for street-running light rail (also referred to as 'tram' or 'streetcar') infrastructure. Based on the 'movement and place' model, this research presents a new framework to define place types served by Melbourne trams, as well as the different tram link types relating to tram infrastructure used to get people to/from those destinations. It implements the framework to the network and explores variation in movement and place framework links including categorisation of links into four tram streetscape groups. Implications of the framework for policy and future research are discussed.